IMPROVING LINGUISTIC COMPETENCE ON THE BASIS OF DIALECTOLOGICAL PRACTICE - Dilbar Uskanovna Duysabayeva; Userbay Alimkhanovich Baykabilov; Jandos Abdazimovich Bayzakov; Nurkeldi Abdurashidug‘li Jarasbaev (The Bioscan, 2024)
As one of the priority areas of modern education, the cultural approach is valuable in that it is aimed at forming a person who has mastered a holistic picture of the world, has mastered the spiritual, moral and cultural values of his national culture. The direction of education in the teaching of the native language and literature is carried out in the cultural approach, which is based on the main idea of linguistics, a rapidly developing branch of linguistics - the inseparability of the connections in the triad "language, culture, society". Therefore, the educational program for the professional training of a future teacher of the native language and literature should ensure his acquisition of linguocultural competence, which is of paramount importance for a philologist as an integral part of his professional competence, and its effectiveness and quality depend on the fulfillment of professional tasks in teaching, development and upbringing. This article discusses the problems of the concepts of "competence" and "linguocultural competence", the importance of dialectological practice in the formation of linguocultural competence. Also, modern approaches to the formation of linguocultural competence in the training of future teachers of the Kazakh language and literature are considered.